A drug utilization study of topical corticosteroids in the department of dermatology in a tertiary care teaching hospital in upper Assam - Syiem, Reuben P.; Chaliha, Meghali; Talukdar, Krishna (International Journal of Basic & Clinical Pharmacology, 2022)
Background: Topical corticosteroids form an important group of drugs in dermatology and are among the most commonly prescribed medications. However, despite their efficacy, they are associated with various adverse effects and as majority of the skin conditions are chronic, there is a need to ensure that there is rationality in drug use. Thus, this study was conducted with an aim to analyze the drug utilization pattern of topical corticosteroids. Methods: The study was a hospital-based, prospective and observational study and conducted for a period of 12 months. The method of data collection was done based on one-on-one consultation with patients. Data collected were recorded prospectively in a specially designed proforma. Results were then entered and analyzed using Microsoft excel. Results: In the study, it was observed that 48% of the patients were males while 52% were females. Most patients belonged to the age group of 21-30 years (30%). Scabies (30%) was the most common dermatological condition. With regard to the prescribing frequency of different topical corticosteroids, mometasone furoate (31.4%) was the preferred choice in most patients. H1 antihistaminic drugs like levocetirizine (81.6%) were the most prescribed along with topical corticosteroids, followed by emollients (36.4%) and permethrin (29.2%). The average number of drugs per prescription was 3.6 and all drugs were prescribed by their generic names. Conclusions: Periodic monitoring of the drug utilization pattern in the form of prescription auditing is an effective tool to constitute guidelines for improving the utilization pattern.